#TITLE_ALTERNATIVE# - KURNIA (NIM 10205069); Pembimbing: Dr. Wahyu Srigutomo, RUDDY
Groom-Bailey decomposition method is a decomposition of magnetotelluric tensor that consider effect of galvanic distortion at shalow subsurface. Galvanic distortion is represented in a distortion tensor which factorized into gain, shear, twist, and anisotropy. The purpose of implementation Groom-Bailey decomposition is to have increasing quality of magnetotelluric data in order to obtain the best representation of subsurface structures. Generally, this final project consists of three main parts, which are explanation of theoretical overview, data processing, analysis of Groom-Bailey decomposition result. In theoretical overview part will explain about basic concept of magnetoteluric method, electromagnetic scattering, distortion model, factorization of distortion tensor, determination of regional and local strike. Data processing part will explain about procedure of calculation, flowchart of decomposition Groom-Bailey codes and representation of decomposition result of magnetotelluric data. Finally, the last part will explain about analysis of distortion parameter, analysis of regional and local strike, and analysis of apparent resistivity and phase impedance. It can be concluded this research that implementation of decomposition Groom-Bailey method to impedance tensor of magnetotelluric will increasing data quality. It means that value of rms error is more less than obtained using conventional method. Result of regional strike decomposed is compatible with regional strike of inducton vector.